Association between HIV Clinical Stage and The Incidence of Opportunistic Infections among HIV/AIDS Patients at Banten Regional Hospital in 2020-2024 - Trasia, Reqgi First; Safitri, Dina Lutfia; Irawati, Nur Bebi Ulfah (Jurnal Medis Islam Internasional, 2025)
Introduction: Untreated HIV conditions can progress to AIDS, which is the terminal phase of HIV infection, making the body more susceptible to other infections called opportunistic infections. Opportunistic infections are generally not dangerous for healthy people but can be fatal if they affect people with immunosuppression, such as HIV/AIDS patients. Objective: This study aims to determine the relationship between HIV clinical stage and the incidence of opportunistic infections among HIV/AIDS patients at Banten Regional Hospital in 2020–2024. Methods: This study is retrospective with a cross-sectional design. The sampling technique used was consecutive sampling, and the sample size calculation used the two-proportion comparison formula. The research data were analyzed univariate and bivariate using SPSS 26.0 Program. The research hypothesis was tested using the Chi-square statistical test and the Mantel-Haenszel Common Odds Ratio Estimate. Results: The respondents in this study were 242 HIV/AIDS patients. The results of the analysis showed that the prevalence of HIV/AIDS at Banten Regional Hospital in 2020-2024 was 0.06%, with the highest proportion being stage I (50.83%), stage III (26.45%), stage IV (14.88%), and stage II (7.85%). The prevalence of opportunistic infections was 45.45%. Of the 110 patients identified as having opportunistic infections, 141 infections were obtained. Some patients had one type of opportunistic infection (81.82%), two types of opportunistic infections (11.82%), and ≥ three types of opportunistic infections (6.36%). The proportion of opportunistic infections based on etiology was dominated by bacterial infections (73.76%), parasitic infections (13.48%), fungal infections (6.38%), and viral infections (6.38%). The most common opportunistic infections suffered by HIV/AIDS patients at Banten Regional Hospital were tuberculosis (44,68%) and toxoplasmosis (9,93%). Conclusions: Based on bivariate analysis, there was a significant relationship between the clinical stage of HIV and the incidence of opportunistic infections among HIV/AIDS patients at Banten Regional Hospital in 2020–2024.